Strategi Kepemimpinan Transformatif dalam Penguatan Budaya Religius di Lembaga Pendidikan Islam - Syaifi, Mat (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study investigates the leadership strategies of principals in fostering religious culture within Islamic senior high schools. Conducted at MAS Sunan Ampel Kejayan and MA Miftahul Ulum Kalirejo in Pasuruan, East Java, the research applies a qualitative multi-site case study approach. Data were collected through interviews, observations, and document analysis, and analyzed thematically. Findings indicate that effective religious culture building is driven by three interrelated strategies. First, principals serve as role models who consistently embody Islamic values through daily practices and moral decision-making. Second, religious values are institutionalized through school policies, integrated curricula, structured programs, and symbolic environments that reinforce spiritual life. Third, leadership is exercised in a participative and responsive manner, teachers, students, and parents are actively involved, and the principals adapt their approaches based on students’ psychosocial contexts. This study affirms that successful religious culture in Islamic schools depends not only on formal instruction but also on the principal’s capacity to lead by example and create a systemic environment that sustains those values. It contributes to the literature on transformational and values-based leadership in Islamic education, with practical implications for leadership training and school development.